Estudio De La Resistencia Al Impacto Del Alabe Para Una Turbina Eólica De 0.5 Kw Ubicada En Playa Blanca - Aguirre Polo, Humberto Gonzalo (2017)
In this research, the wind turbine blade of 0.5 Kw was studied to improve its internal resistance under impact. This thesis was based on the problem of wind turbine blade breakages, due both to bird impacts and strong winds. During breakages, blade parts thrown at speed from the rotating turbine pose a significant risk to residents. This research aimed to improve the design of the blades, to improve the blade impact resistance and reduce risk to turbine users. This was desired wthout modifying the airfoil profile, weight, balance, and without significantly modifying construction methods. Two improved designs were investigated, with metal plate and with steel wire, over the full length of the blade. A new experimental test rig was designed to carry out 3 tests to analyse the new blade designs and compare them with the original design. The three tests performed were bending, lateral impact and frontal impact. The original blade design, with no internal support, snapped and seperated during impact testing. Both improved designs withstanded higher forces in all testing, and did not let parts of the blade separate after impact, significantly reducing risk for turbien users. The steel plate design showed less damage than the steel wire design. Both new designs show significant improvements, thoghh the steel plate design is recommended as performed better on all 3 tests conducted.